Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1515/jpem.2005.18.11.1031
|View full text |Cite
|
Sign up to set email alerts
|

Growth Monitoring and Diagnostic Work-up of Short Stature: An International Inventorization

Abstract: Background/Aims: Growth monitoring is almost universally performed, but few data are available on which referral criteria and diagnostic work-up are used worldwide for children with short stature. Methods: A short questionnaire, containing questions on auxological screening and on diagnostic criteria for short stature, was sent to all members of the European Society of Paediatric Endocrinology (ESPE) and to several pediatric endocrinologists outside Europe. Results: Responses were received from 36 countries. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 5 publications
1
36
0
1
Order By: Relevance
“…There is no consensus about which systemic disorders should be excluded, and how this should be done, before the ''diagnosis" ISS is made [36]. It obviously depends on the skills of the clinician whether (s)he performs a thorough medical history, physical examination, and laboratory screening to exclude known causes of short stature.…”
Section: Systemic Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…There is no consensus about which systemic disorders should be excluded, and how this should be done, before the ''diagnosis" ISS is made [36]. It obviously depends on the skills of the clinician whether (s)he performs a thorough medical history, physical examination, and laboratory screening to exclude known causes of short stature.…”
Section: Systemic Diseasesmentioning
confidence: 99%
“…For screening purposes, many clinicians evaluate three parameters of growth: (1) the child's height compared with the best reference available, leading to the height position (SDS or percentile) of the child compared with the population reference; (2) the child's height SDS compared with target height SDS based on parental height, and (3) the child's growth curve based on previous growth data in terms of slowed growth (growth deflection, growth faltering), crossing the SD or percentile lines, leading to a parameter of growth velocity either expressed as cm/year or SDS, or delta height SDS [36]. It was recently reported that an auxological screening guideline in terms of growth velocity, would lead to far too many referrals [121] and that the distance between height SDS and target height SDS is a better screening parameter for Turner syndrome and other pathology than height SDS as such or the change in height SDS over time [101,102], although a reported parental height has a rather low accuracy [122].…”
Section: What Are the Criteria To Initiate Investigation In Short Patmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Further evaluation of pathological short stature is done as per various etiologies. 5,6 Familial short stature and Constitutional Growth delay are considered as normal variants. 7 While the pathological short stature includes a wide variety of underlying disorders.…”
Section: Introductionmentioning
confidence: 99%
“…However, RTA is a rare condition, and in a retrospective analysis of 742 short children no case with RTA was found (although the compliance with the guideline was far from optimal) [8] . Among pediatric endocrinologists there is no worldwide consensus about including this test in the screening procedure for growth failure: only 32% of the participating pediatric endocrinologists considered blood gas analysis important in the evaluation of a child with failure to thrive [9] .…”
Section: Introductionmentioning
confidence: 99%